2003
DOI: 10.1159/000074546
|View full text |Cite
|
Sign up to set email alerts
|

Phagocytosis and Allogeneic T Cell Stimulation by Cultured Human Osteoblast-Like Cells

Abstract: Background/Aims: The antigen phenotype of human osteoblast-like cells suggests that they are related to other cellular populations and may also have immunologic functions in common. Methods: Flow cytometry and transmission electron microscopy were used to show the phagocytotic activity of osteoblast-like cells in culture. The allogeneic stimulation of T cells by human osteoblast-like cells was determined by the measurement of T cell proliferation. Results: We demonstrated in vitro that human osteoblast-like ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 17 publications
(31 reference statements)
0
34
1
Order By: Relevance
“…Given that other resident macrophage populations have important tissue-specific functions (4), we investigated the potential bone-specific functions of OsteoMacs in the osteal microenvironment. We first determined whether immune-related functions that were attributed to osteoblasts using primary cultures as the model system (11,12) may in fact be mediated by the coisolated macrophages and provided evidence supporting that this is the case for LPS responsiveness. Osteoblast cell lines have been reported to be LPS responsive but the concentration of LPS used was very high (12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that other resident macrophage populations have important tissue-specific functions (4), we investigated the potential bone-specific functions of OsteoMacs in the osteal microenvironment. We first determined whether immune-related functions that were attributed to osteoblasts using primary cultures as the model system (11,12) may in fact be mediated by the coisolated macrophages and provided evidence supporting that this is the case for LPS responsiveness. Osteoblast cell lines have been reported to be LPS responsive but the concentration of LPS used was very high (12).…”
Section: Discussionmentioning
confidence: 99%
“…Calvarial osteoblast preparations are morphologically heterogeneous (10), but their reported phenotypes and functions are generally attributed to the osteoblast component of these cell preparations. This includes macrophage-related functions such as phagocytosis (11), detection of bacterial products (12), and Ag presentation (11). As studies of long-term primary cultures from ovary have been demonstrated to contain a selfreplicating monocyte-macrophage population (13), and macrophages are located within the bone microenvironment (6), we considered the possibility that macrophages are coisolated and maintained in primary osteoblast cultures.…”
mentioning
confidence: 99%
“…Besides their essential role in bone formation and repair, osteoblasts possess immunological functions, including T lymphocyte stimulation, phagocytic activity, and cytokine synthesis [15][16][17][18][19][20][21][22][23]. Osteoblasts express CD54, CD80, CD86, and HLA-DR surface antigens according to their degree of differentiation and/or activation, and their antigenic profile is modulated by the presence of different cytokines and growth factors [17,18,22].…”
Section: Introductionmentioning
confidence: 99%
“…The bacteria capable of degrading NB, such as Pseudomonas pseudoalcaligenes (Nishino and Spain 1993), Comamonas sp. Zhao and Ward 1999), Acidovorax delafieldii (Zhao and Ward 1999), Pseudomonas putida (Park et al 1999;Li et al 2007) and Mycobacterium chelonae (Oh et al 2003), have been isolated from contaminated soils and wastewater in the past decades. Moreover, NB is known to be metabolized by aerobic bacteria through either a partial reductive pathway characterized by the release of ammonia (Nishino and Spain 1993;Park et al 1999) or an oxidative pathway characterized by the release of nitrite .…”
Section: Introductionmentioning
confidence: 99%